Marked paper: Type 2 diabetes mellitus indicates increased postoperative complications and poor prognosis in colorectal cancer patients receiving curative surgery - Liu, Daoli; Zhang, Xubing; Zhou, Hong; Zhu, Zhiqiang; He, Yiren; Wan, Xiao; Zhang, Bo; Liu, Shaojun; Liu, Liu (Frontiers in Oncology, 2023)
Purpose: This study aimed to evaluate the impact of type 2 diabetes mellitus (T2DM) on the short-term outcome and long-term survival of patients with colorectal cancer (CRC) who underwent curative resection. Methods: This study retrospectively included 136 patients (T2DM group) with resectable CRC and T2DM from Jan 2013 to Dec 2017. Propensity score-matched control group consisting of 136 patients (non-T2DM group) were selected from 1143 CRC patients. The short-term outcomes and prognosis were compared between the T2DM and non-T2DM group. Results: A total of 272 patients (136 patients for each group) were included in this study after propensity score matching for gender. Patients in T2DM group had higher body mass index (BMI), higher proportion of hypertension and cerebrovascular diseases (P<0.05). T2DM group had higher overall complications (P=0.001), higher major complications (P=0.003) and higher reoperation (P=0.007) when compared with non-T2DM patients. T2DM patients had longer-time hospitalization than non-T2DM (20.7±10.2 vs. 17.5±6.2, P=0.002). As for prognosis, T2DM patients had worse 5-year overall survival (OS) (P=0.024) and 5-year disease-free survival (DFS) (P=0.019) in all stage. Moreover, T2DM and TNM stage were independent predictors of OS and DFS. Conclusions: T2DM increases overall complications and major complications after CRC surgery. In addition, T2DM may indicate poor prognosis of CRC patients. A prospective study with large sample size is required to further confirm our findings.